STIMULATING GRASS-ROOTS INTEREST IN HIGHLAND CULTURE - Valerie Anne, Mashman; Roger, Harris (UNIMAS Publisher, 2017)
The Highlands in the Heart of Borneo are home to several distinctive and related indigenous cultures. In Sarawak, these include the Kelabit, Lun Bawang, Sa’ban and Penan. In the neighbouring province of Kalimantan, Indonesia there are the Krayan, Brian, Merau , Berau or Sa’ban, Miyau or Lengilu’, Nyibun and Potok (also known as Putok) peoples, all collectively known as the Lun Daye of East Kalimantan. In both Malaysia and Indonesia, these peoples exist as minorities within populations whose cultures and lifestyles are different from theirs. According to the United Nations Permanent Forum on Indigenous Issues, cultural rights are of particular relevance for indigenous minority peoples given that they are culturally distinct from their neighbouring majority societies which tend to be politically dominant. Cultural rights involve protection for traditional and religious practices, languages, sacred sites, cultural heritage, intellectual property, and oral and traditional history. The cultural rights of indigenous peoples are guaranteed in various international instruments. The UN Declaration on the Rights of Indigenous Peoples is the foremost instrument on indigenous peoples’ rights. It articulates how economic, social and cultural rights apply in the context of indigenous peoples, and it points out the necessity of considering their cultural rights in light of the principles of self-determination and non-discrimination. But what if a culture is disappearing? How can cultural rights be protected if indigenous peoples are unaware of the need to protect them? National Geographic explorer Wade Davis suggests that westerners see traditional societies as failed attempts at modernity that are destined to disappear because they can't change. He argues that this is completely wrong. If the chief measure of success of a society is technological wizardry, then first world culture would win. But if the criterion is the capacity to thrive sustainably, and the world is moving in this direction, then first world cultures would fail. In a truly diverse world, he argues, the spread of beneficial technology, like the Internet, need not imply the assimilation and elimination of minority endangered cultures. For us at the Knowledge Fair, we totally endorse this view. The following box describes how Kelabit culture is in danger of disappearing.